Transforming Civil Construction: Environmental seal as a mark of sustainable commitment - Marques, Maurício Dias; Junior, Sérgio Silva Braga; Simões, Rebeca Delatore (Seven Editora, 2024)
Sustainable Civil Construction, also referred to as green construction or green construction, seeks environmental certification as evidence of efficient evaluation in its process. Allied to this purpose, environmental certification seals play a crucial role. This article aims to present a compilation of information and considerations from several authors regarding the certificates available and most used in Brazil, to assist those who seek to validate their civil construction works with sustainable requirements. The origins and main characteristics of each seal are described. As a result, a table was developed that synthesizes information about each seal regarding the date of appearance, origin, responsible entity, categories and evaluation criteria, classification levels, among other aspects. Thus, this document offers, in a consolidated way, valuable information for decision-making in relation to the choice of certification, providing ease for those seeking certification and encouraging new research in the field. DOI:https://doi.org/10.56238/sevened2024.010-035